Expressões nominais referenciais em editoriais: foco na paragrafação - Santos, Cristiano Pereira Miranda dos (2008)
This dissertation is going to discuss the use of referential expressions as cognitive markers of paragraphs and organisers of textual macrostructure of newspaper editorials. In the perspective of discourse reference (MONDADA; DUBOIS, 1995, 2003), this paper aims to analyse like referential expressions can contribute to the writing of paragraphs, specially, to the writing of newspaper editorials. This analysis is based on studies of Textual Linguistics whose position considers the text as an activity of social interation. Specifically, it is base on studies of discourse reference as process of generate discourse referents. The corpus consists of ten editorials published in the newspaper Folha de S. Paulo in 2007. The results suggest that referential expressions contribute to the writing of paragraphs of newspaper editorials